The Impact of Artificial Intelligence on Social Cohesion - Al-Raeesi, Roqaya Cheragh; ELnemr, Amal Zakaria Mancy; Matalka, Faisal Al; Ahmed, Asmaa; Alamiri, Amina Ibrahim (Journal of Posthumanism, 2025)
The study has the objective of examining the effects of artificial intelligence on social cohesion in the context of using a qualitative analytical research approach that combines theoretical review with semi-structured interviews with (23) social workers in the Emirate of Sharjah. The research is looking to contribute to an enhanced understanding of the adoption of artificial intelligence in social cohesion, as well as identifying the potential benefits and challenges hindering its adoption effectively. The findings of the study showed a significant congruence with the current academic literature, as theoretical discussions have highlighted the high potential of artificial intelligence to improve the quality of social services through the analysis of big data, provision of evidence-based advice, and facilitation of access for the beneficiaries. However, this study identified a number of important problems, such as legal and ethical challenges posed by algorithmic bias, privacy breaches, and a lack of transparency in decision-making processes based on artificial intelligence. Additionally, the interviews identified a knowledge gap between technical developers and social workers, which prevents a full understanding of algorithmic processes and their implications for social decision-making. The findings showed an urgent need for the creation of clear-cut regulatory policies aimed at leveraging artificial intelligence in promoting social cohesion, as well as the introduction of specialized training programs aimed at enhancing the technical and professional competencies of social workers. The study promotes an overall framework that encompasses the development of legal frameworks, the development of technical capabilities, and the strengthening of cooperation between practitioners and developers, with the goal of finding a balance between technological progress and humanitarian values in promoting social cohesion.